QUANTITATIVE INDICATORS OF NITROGEN OXIDES WHEN USED AT DIFFERENT ENERGY INSTALLATIONS - Sheleshey, Tetiana; Bednarska, Inna; Kutsa, Alina; Tsyhanov, Kirill; Olуmenko, Iryna; Apostol, Yaroslav (Sworld-Us Conference proceedings, 2023)
The article deals with the harmful effects of nitrogen oxides on the environment. The list of primary (technological) measures aimed at reducing the formation of nitrogen oxides in the furnace or combustion chamber of the boiler: low-toxic burners, step a